Enzymatic protein hydrolysates from high pressure-pretreated isolated pea proteins have better antioxidant properties than similar hydrolysates produced from heat pretreatment. (1st December 2015) - Girgih, Abraham T.; Chao, Dongfang; Lin, Lin; He, Rong; Jung, Stephanie; Aluko, Rotimi E.
Highlights: ORAC of protein hydrolysates was improved after 400 and 600 MPa pretreatment of pea protein. DPPH radical scavenging by hydrolysates was improved after 400 MPa pretreatment of pea protein. Heat pretreatment of pea protein resulted in reduced DPPH scavenging by the hydrolysate. Heat pretreatment of pea protein resulted in improved ferric reducing power of hydrolysate. Abstract: Isolated pea protein (IPP) dispersions (1%, w/v) were pretreated with high pressure (HP) of 200, 400, or 600 MPa for 5 min at 24 °C or high temperature (HT) for 30 min at 100 °C prior to hydrolysis with 1% (w/w) Alcalase. HP pretreatment of IPP at 400 and 600 MPa levels led to significantly ( P < 0.05) improved (>40%) oxygen radical absorption capacity (ORAC) of hydrolysates. 2, 2-Diphenyl-1-picrylhydrazyl, superoxide radical and hydroxyl radical scavenging activities of pea protein hydrolysates were also significantly ( P < 0.05) improved (25%, 20%, and 40%, respectively) by HP pretreatment of IPP. Protein hydrolysates from HT IPP showed no ORAC, superoxide or hydroxyl scavenging activity but had significantly ( P < 0.05) improved (80%) ferric reducing antioxidant power. The protein hydrolysates had weaker antioxidant properties than glutathione but overall, the HP pretreatment was superior to HT pretreatment in facilitating enzymatic release of antioxidant peptides from IPP.